Recurrence Formula of Stamp Folding Problem (Global Journal of Science Frontier Research, 2023)
There is an unsolved problem that has plagued mathematicians for a long time, the "stamp folding problem" (strictly, is there a formula for counting the solutions to the stamp folding problem?). In this paper, I have succeeded in expressing the stamp-folding problem by a recurrence formula with an elegant idea.
Keywords: stamp folding problem; discrete mathematics; discrete geometry; folding; crease